Analysis Of Rice Farmers Income (Cultivators) On Profit Sharing System In Moyo Hilir, Sumbawa Districts In 2022 - Arifin, Zainal; Baharuddin, Baharuddin; Kusumawati, Indra (International Journal of Educational Research & Social Sciences, 2022)
This research is entitled Analysis of Rice Farmers' Income (Cultivators) in the Profit Sharing System in Moyo Hilir, Sumbawa Districts in 2022. The purpose of this study was to determine the income of farmers in the profit sharing system in Moyo Hilir, Sumbawa District in 2022 and to find out the income of farmers in the profit sharing system in Moyo Hilir, Sumbawa District in 2022, is above or below the need for a decent living. The data collection uses sample survey method, which is a method of data collection carried out by withdrawing part of the population unit that is considered to represent the characteristics of the population in question (Moh. Nazir, 1999). Results of Analysis Data obtained by cultivators in Moyo Hilir, Sumbawa District, based on the average level of fulfillment of needs for each cultivator farmer, is only able to meet the needs of a decent life of 32,961 percent. with a profit sharing system in Moyo Hilir, Sumbawa District and is classified as farmers who are not yet prosperous based on the results of research conducted on 11 respondents as research samples. The conclusion from the results of the study is that there is not a single cultivator farmer who is able to meet the financing of their decent living needs up to 100 percent. The contribution of their net income from profit-sharing agricultural products in meeting the needs of a decent life ranges from 31.14 percent to 55.89 percent only. Based on the results of the study, the net income received by cultivator farmers who are used as respondents can be said to be sufficient to meet the needs of life. The highest net income is 2,757,332 rupiah per month, while the lowest net income after profit sharing is 2,103,365 rupiah per month. With an average net income per month of 2,387,295 rupiah, cultivators already feel prosperous and sufficient with their income. However, there are also some farmers who say that they are not yet prosperous or not satisfied with their income. Statistically based on the KHL standard of Sumbawa District, on average each Cultivator in Moyo Hilir, Sumbawa District is still classified as not prosperous. This is because the income of cultivators in the profit-sharing system is still far below the Standard of Kebutuhan Hidup Layak (KHL).